2013
DOI: 10.1016/j.comgeo.2012.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Large convex holes in random point sets

Abstract: A convex hole (or empty convex polygon) of a point set P in the plane is a convex polygon with vertices in P , containing no points of P in its interior. Let R be a bounded convex region in the plane. We show that the expected number of vertices of the largest convex hole of a set of n random points chosen independently and uniformly over R is Θ(log n/(log log n)), regardless of the shape of R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…This is in contrast with the fact that, unlike Horton sets, they contain arbitrarily large holes. Quite recently, Balogh, González-Aguilar, and Salazar [3] showed that the expected number of vertices of the largest hole in a set of n random points chosen independently and uniformly over a convex body in the plane is in Θ(log n/(log log n)).…”
Section: Islands and Holes In Random Point Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast with the fact that, unlike Horton sets, they contain arbitrarily large holes. Quite recently, Balogh, González-Aguilar, and Salazar [3] showed that the expected number of vertices of the largest hole in a set of n random points chosen independently and uniformly over a convex body in the plane is in Θ(log n/(log log n)).…”
Section: Islands and Holes In Random Point Setsmentioning
confidence: 99%
“…FIGURE 5 An illustration of the proof of Lemma 10. In order for {p 1 , … , p i } to be an i-island in S, the light gray part cannot contain points from S. We estimate the probability of this event from above by the probability that the dark gray simplex conv(𝜑 ∪ {p i }) contains no point of S. Note that the parameters 𝜂 and 𝜏 coincide for 𝑑 = 2, as then…”
mentioning
confidence: 99%
“…, for some constant K. Balogh et al [5] showed that the expected number of vertices of the largest empty convex polygon in S is Θ( log n log log n ).…”
Section: Introductionmentioning
confidence: 99%
“…In [2], Balogh et al proved that w.h.p. the size of the largest (in the number of vertices) polygonal hole with vertices in K n is Θ(log n/ log log n).…”
Section: Introductionmentioning
confidence: 99%